2002
DOI: 10.1159/000067292
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ras-Mediated Cell Proliferation by Benzyloxybenzaldehyde

Abstract: Excessive proliferation of vascular smooth muscle cells (VSMC) in the intima is an important etiologic factor in vascular proliferative disorders such as atherosclerosis and restenosis after balloon angioplasty. Therefore, control of VSMC growth may be a suitable therapeutic intervention in vascular proliferative disorders. In the present work, we have studied the 2-benzyloxybenzaldehyde (CCY1a)-mediated antiproliferative effect and its mechanisms of action. CCY1a inhibited serum-induced VSMC proliferation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition, 2-benzyloxybenzaldehyde can block Ca 2+ entry and suppress formyl peptide-stimulated increase in intracellular Ca 2+ in neutrophils (28). Pan et al (29) demonstrated that 2-benzyloxybenzaldehyde modulates vascular smooth muscle cell proliferation by blocking the Ras/p42/44 MAPK pathway and inhibiting NF-κB and AP-1 DNA binding activities. Our previous study showed that CCY-1a-E2 reduced the percentage of viable murine leukemia WEHI-3 cells, and the IC 50 value of CCY-1a-E2 was 5 µM for a 24-h treatment (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2-benzyloxybenzaldehyde can block Ca 2+ entry and suppress formyl peptide-stimulated increase in intracellular Ca 2+ in neutrophils (28). Pan et al (29) demonstrated that 2-benzyloxybenzaldehyde modulates vascular smooth muscle cell proliferation by blocking the Ras/p42/44 MAPK pathway and inhibiting NF-κB and AP-1 DNA binding activities. Our previous study showed that CCY-1a-E2 reduced the percentage of viable murine leukemia WEHI-3 cells, and the IC 50 value of CCY-1a-E2 was 5 µM for a 24-h treatment (19).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 2-benzyloxybenzaldehyde exhibited antiproliferative effects on the vascular smooth muscle cells through the inhibition of the Ras/MAPK signal pathway and its downstream effectors (9). It has also been demonstrated that 2-benzyloxybenzaldehyde inhibits superoxide anion generation through the suppression of Akt and PLD activation in rat neutrophils (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Cultured VSMCs were lysed in a standard lyses buffer. The cell lysate was centrifuged and the supernatant was used for the Western blotting analysis as described previously (19). ERK1/2 and phosphorylated ERK1/2 antibodies (Santa Cruz Biotechnology) diluted 1 : 1000 in phosphate-buffered saline (PBS), were used as primary antibodies and were applied for overnight incubation at 4°C.…”
Section: Western Blot Analysismentioning
confidence: 99%